Pharmacokinetics, Safety, and Tolerability of Amygdalin and Paeoniflorin After Single and Multiple Intravenous Infusions of Huoxue-Tongluo Lyophilized Powder for Injection in Healthy Chinese Volunteers - Li, Xiaobing; Shi, Fuguo; Zhang, Run; Sun, Chenglong; Gong, Chuting; Jian, Lingyan; Ding, Li (Clinical therapeutics, 2016)
Huoxue-Tongluo lyophilized powder for injection (HTLPI), a traditional Chinese medicine preparation, is a compound of Persicae semen and Paeoniae Radix Rubra that is used mainly for treating blood-stasis obstruction syndrome in the acute stage of cerebral ischemic stroke. Amygdalin (AD) and paeoniflorin (PF) are 2 typical bioactive components in HTLPI and were selected as indicators for this pharmacokinetic study of HTLPI. The objective of this study was to investigate the safety profile, tolerability, and pharmacokinetic properties of AD and PF after single and multiple intravenous infusions of HTLPI in healthy Chinese volunteers. Twenty-one healthy Chinese subjects were recruited for this open-label, single ascending-dose (3, 6, and 9 g) and multiple-dose (6 g, once daily) study. Safety profile was assessed by adverse events and physical examination throughout the study. Serial plasma and urine samples were analyzed by HPLC-MS/MS. Pharmacokinetic parameters of AD and PF were calculated using noncompartmental analysis. In the single-dose phase of the study, the mean maximum plasma concentration and the mean area under the plasma concentration−time curve of AD and PF increased proportionally with each dose escalation. In the multiple-dose phase, the steady state was achieved by day 4 after multiple-dose administration of 6 g HTLPI. Mean pharmacokinetic parameters achieved on day 1 were similar to those on day 7. No significant accumulation was observed after repeat doses of 6 g HTLPI. Approximately 79.6% of the administered AD and 48.4% of the administered PF were excreted unchanged in urine within 24 hours. No serious adverse events were observed during the entire study. The pharmacokinetic properties of AD and PF were linear after a single intravenous infusion of HTLPI in the dose range of 3−9 g. No systemic accumulation was observed with repeat doses of HTLPI. Sex had no significant effect on the pharmacokinetic properties of AD and PF. Intravenous infusion of HTLPI was well tolerated in healthy Chinese subjects.